Control of Freedom Principle Contract in the Pre Project Selling System (Research, Society and Development, 2020)
The Pre Project Selling is sale before project was built where the property being sold is just a picture or concept. This marketing concept has become a trend in the modern era, especially for the Developer. The freedom principle of contract in an agreement is a must-have foundation in terms of agreements in the pre-project selling transactions. In customer contract made in the standard writing form that has been previously ready by developer. This means that all the term and condition has been made by the developer itself, and then the consumer will only do so need to approve or reject the contract without the ability to change or add anything to the PPJB content. Those agreements are commonly not considering enough the interests of other parties so it is being questioned whether it still gives consumers freedom. The absence of rules regarding Pre Project Selling in the Statutory Regulation that applicable to made controlling consumer protection is not optimal. The Government needs to make regulations on this matter.